(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
International standards for the design, type-classification and certification of marine energy systems, including wave and current energy converters, are essential for the commercialization of these technologies, but their compliance requires significant effort and resources by project developers; e.g., finding the appropriate met-ocean datasets, processing and analysing this data to estimate the design load conditions, design type-class and load response. Herein we present efforts to address these challenges by developing, beta-testing and demonstrating a web-based tool, the “Design Load Case (DLC) Generator.” This tool integrates a host of data search, processing and statistical tools to streamline the analysis of design load conditions and to determine the design load requirements as in the International Electrotechnical Commission (IEC) 62600-2 design standard. It is demonstrated for a test DLC analysis case for the Reference Model 3 (RM3) point absorber at the PacWave South test site. This test case highlights some of the challenges determining design load requirements and the benefits of facilitating a complex workflow within a single web-based platform that leverages a diverse set of data processing and statistical tools. The DLC Generator facilitates and streamlines DLC analyses for significant time and cost savings on a variety of tasks in a complex workflow, including site data search and retrieval, data quality control, extreme value statistical analyses, and archiving of dynamic load response model inputs and outputs.